Tourism research in China : themes and issues - Huang, Songshan, ....-; Chen, Ganghua, ....- (Bristol : Channel View Publications, 2016)
This book provides critical in-depth reviews on key themes and issues in tourism research in China. These themes include: Chinese scholars' epistemological views of tourism, rural tourism development, community participation in tourism, tourist market and behaviour, tourist attraction management and tour guiding and interpretation in China. While Chinese scholars are often able to access key research in both English and Chinese, the majority of researchers from outside China without knowledge of the Chinese language are unable to read original research from China. This book seeks to redress this knowledge imbalance and bring key Chinese tourism research to the international tourism academic community. This book will be a valuable reference for tourism researchers, postgraduate students and industry.
Includes bibliographical references and index.
Keywords: Tourism -- Research -- China